2018
DOI: 10.1002/ece3.4056
|View full text |Cite
|
Sign up to set email alerts
|

The genetic network of greater sage‐grouse: Range‐wide identification of keystone hubs of connectivity

Abstract: Genetic networks can characterize complex genetic relationships among groups of individuals, which can be used to rank nodes most important to the overall connectivity of the system. Ranking allows scarce resources to be guided toward nodes integral to connectivity. The greater sage‐grouse (Centrocercus urophasianus) is a species of conservation concern that breeds on spatially discrete leks that must remain connected by genetic exchange for population persistence. We genotyped 5,950 individuals from 1,200 gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 77 publications
0
39
0
Order By: Relevance
“…Telemetry records have shown that eastern migratory animals overlap seasonally with boreal animals in Ontario (Berglund et al, 2014;Pond, Brown, Wilson, & Schaefer, 2016). Our network analysis allowed for the calculation of node metrics, which can be used to identify hubs of connectivity and prioritize areas for management (Cross et al, 2018;Garroway et al, 2008;Koen et al, 2016). Our network analysis allowed for the calculation of node metrics, which can be used to identify hubs of connectivity and prioritize areas for management (Cross et al, 2018;Garroway et al, 2008;Koen et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Telemetry records have shown that eastern migratory animals overlap seasonally with boreal animals in Ontario (Berglund et al, 2014;Pond, Brown, Wilson, & Schaefer, 2016). Our network analysis allowed for the calculation of node metrics, which can be used to identify hubs of connectivity and prioritize areas for management (Cross et al, 2018;Garroway et al, 2008;Koen et al, 2016). Our network analysis allowed for the calculation of node metrics, which can be used to identify hubs of connectivity and prioritize areas for management (Cross et al, 2018;Garroway et al, 2008;Koen et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, that ecotype potentially interbreeds with boreal animals and their greater mobility likely increases gene flow within and among boreal caribou sampled areas (Thompson, ), which is similar to findings in Quebec (Boulet, Couturier, Côté, Otto, & Bernatchez, ). Our network analysis allowed for the calculation of node metrics, which can be used to identify hubs of connectivity and prioritize areas for management (Cross et al, ; Garroway et al, ; Koen et al, ). We found that most node metrics based on F ST suggested that sampled areas in northern regions of the Ontario boreal range may be important for supplementing southernmost populations (see Appendix , Table ).…”
Section: Discussionmentioning
confidence: 99%
“…We classified each experimental site in one of two categories based on the type of disturbed nodes in the pre‐disturbance network: if at least one hub was disturbed, the site was categorized as hub disturbed; otherwise, it was categorized as non‐hub disturbed. A node was identified as a hub when its degree was larger or equal to the 90th percentile of the degree distribution obtained from predicted degree of all visited patches in the 10 experimental sites (Bishop‐Taylor, Tulbure, & Broich, , ; Cross et al, ). In total, four sites out of 10 were hub disturbed.…”
Section: Methodsmentioning
confidence: 99%
“…Once genetic graphs have been created, the compute_node_metric function computes graph‐theoretic metrics such as the degree, closeness and betweenness centrality indices, which identify keystone hubs of genetic connectivity (Cross et al., 2018). It also computes the average and sum of the inverse genetic distance weighting the links.…”
Section: Workflowmentioning
confidence: 99%